PEMBUATAN MEDIA PROMOSI BOOKLET DENGAN MENGGUNAKAN APLIKASI CANVA UNTUK MENARIK MINAT BELI DI KARTO AGRO BLITAR - Hayyun Nurvie, Amarida; Joni Dwi Pribadi (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
The purpose of this research is to make booklet as other promotion media to attract buying interests of consumers by using Canva. The research was action research and the data collection methods were interviews, observation, documentation, and questionnaires. The questionnaires were distributed to 33 respondents, including two graphic design experts, one owner, and 30 potential consumers. The questionnaire results were then analyzed by EPIC Model. After that, there was an interview with 5 potential consumers as the respondents to know their buying interests after saw he booklet. The questionnaire data analysis results of the design effectiveness showed that the score was 4.56, which meant very effective. And the interview results showed that booklet can affect buying interest of potential consumers. Based on the results of this research, it can be concluded that the Karto Agro booklet was effective as promotion media and able to attract buying interest of potential consumers.